TEACHING PERFORMANCE OF CEBU TECHNOLOGICAL UNIVERSITY ARGAO FACULTY - Camello, Lynnette Matea S.; Dayaganon, Crysali Therese R.; Elladora, Suzette T.; Carreon, Marichou L. (Journal of Agriculture and Technology Management, 2018)
This paper highlights to determine any relationship betweem faculty-related factors and teaching performance of the faculty members of Cebu Technological University - Argao Campus for SY 2011-2012 based from student's assessment survey (SAS). Specifically this study attempted to determine the faculty teaching performance in relation to the faculty members' age, gender, highest educational attainment, teaching experience, teaching load, status of employment, and the department where teh faculty belongs. The study made use of an analytical-descriptive method of research utilizing the data taken from the latest results of the student's assessment survey (SAS) of teacher's performance. An ISO standard form for student's evaluation on teaching performance. An ISO standard form for student's evaluation on teaching performance was used an instrument of the study. To get reliable and valid results, a universal sampling technique was employed, where all the faculty of CTU Argao were the subjects of the study. Statistics like frequency, and percentage were used to describe the weighted mean for the interpretation of the level of faculty teaching performance and to assess the related factors that influence the performance of the faculty, Chi-square using coefficient of contingency was used. Results revealed that the factors age, teaching experience, academic rank, highest educational attainment, and teaching load, had a significant relationship on the teaching performances of the faculty members. However, gender, status of employment, and the department where the faculty belong have no bearing on the teaching performance. Teaching performance is critical in the teaching-learning process. It can be deduced that the teaching performances of the faculty members of Cebu Technological University - Argao Campus can be affected by some identified factors, thus, an intervention scheme is recommended for adoption.